Workshop Pengembangan Soal AKM Literasi Membaca pada MGMP Bahasa Indonesia SMA Kabupaten Kampar - Muhammad Mukhlis; Wilda Srihastuty Handayani Piliang; Supriyadi; Latif; Hermaliza; M. Arsyat Rohimakumullah; Pretty Fahra Nabila; Sudirman Shomary (UIR Press, 2022)
The implementation of this service was motivated by the many complaints from Indonesian language teachers who were collected in the MGMP SMA Kampar Regency who had difficulty in making the Minimum Competency Assessment (AKM) reading literacy questions. The strategy used in this PKM is to conduct workshops. The first step is that participants are given an understanding of concepts in developing AKM questions. Next, participants were asked to make AKM questions which were then discussed. The results of this service are expected that participants can understand and develop the AKM Reading Literacy questions. Based on the implementation of the workshop on the Development of AKM Reading Literacy Questions at the Indonesian Language MGMP at SMA Kampar Regency, it can be concluded that the activity went smoothly and successfully. Participants have been able to make AKM reading literacy questions based on predetermined provisions. Based on the assignments given to the MGMP teachers, information was obtained that participants had been able to develop reading literacy questions. Furthermore, from filling out the partner satisfaction questionnaire, it can be concluded that the average participant is satisfied with the activities carried out.